Thermogravimetric kinetic modelling of in-situ catalytic pyrolytic conversion of rice husk to bioenergy using rice hull ash catalyst - Loy, A.C.M. (Elsevier Ltd, 2018)
The thermal degradation behaviour and kinetic parameter of non-catalytic and catalytic pyrolysis of rice husk (RH) using rice hull ash (RHA) as catalyst were investigated using thermogravimetric analysis at four different heating rates of 10, 20, 50 and 100 K/min. Four different iso conversional kinetic models such as Kissinger, Friedman, Kissinger-Akahira-Sunose (KAS) and Ozawa-Flynn-Wall (OFW) were applied in this study to calculate the activation energy (EA) and pre-exponential value (A) of the system. The EA of non-catalytic and catalytic pyrolysis was found to be in the range of 152â190 kJ/mol and 146â153 kJ/mol, respectively. The results showed that the catalytic pyrolysis of RH had resulted in a lower EA as compared to non-catalytic pyrolysis of RH and other biomass in literature. Furthermore, the high Gibb's free energy obtained in RH implied that it has the potential to serve as a source of bioenergy production. Â© 2018 Elsevier Ltd